2014
DOI: 10.5815/ijmecs.2014.05.03
|View full text |Cite
|
Sign up to set email alerts
|

Free Open Source Software in Electronics Engineering Education: A Survey

Abstract: Since the last two decades, much attention has been paid to Electronics Engineering (EE) education in India. Various commercial software tools and simulator such as mathematical application packages, electronics CAD tools, learning management systems, multimedia tools and general purpose tools supports EE education. Traditionally, proprietary software packages such as OrCAD Pspice, MATLAB, LabView, Multisim and others too are widely practiced and well integrated in electronics engineering curricula of various … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 13 publications
0
12
0
Order By: Relevance
“…Despite the power of computer-based learning, research by Chou and colleagues has shown the importance of face-to-face teaching, and the importance of evaluating combinations of learning methods [10]. There are also numerous studies on the commuter-based learning for computing areas such as open source [11], computer programming [12], web learning [13] and so forth. Much research has been conducted on different forms of web-based learning such as e-learning [14], and effectiveness of MOODLE [15].…”
Section: Related Work In Mindfulness Traningmentioning
confidence: 99%
“…Despite the power of computer-based learning, research by Chou and colleagues has shown the importance of face-to-face teaching, and the importance of evaluating combinations of learning methods [10]. There are also numerous studies on the commuter-based learning for computing areas such as open source [11], computer programming [12], web learning [13] and so forth. Much research has been conducted on different forms of web-based learning such as e-learning [14], and effectiveness of MOODLE [15].…”
Section: Related Work In Mindfulness Traningmentioning
confidence: 99%
“…The teaching and learning processes are enhanced by educational technologies [62]. In addition, technology enabled assessment tasks provide paperless test distribution, immediate feedback on student-submitted course work, and foster student motivation and interest in learning [49,50].…”
Section: Impact Of Educational Technologiesmentioning
confidence: 99%
“…Vijay Nehra et. al have documented some open source EDA tools [8]. Few other EDA tools available in the market are LTSpice [7], QUCS [4] and e-Sim [9].…”
Section: Proposed Research Workmentioning
confidence: 99%